Assessment of hydrological factors affecting shallow groundwater chemistry in the most urbanized area of the coastal sedimentary basin of Togo - K. V. Akpataku (Copernicus Publications, 2021)
The project to reduce environmental and health risks related to the activity of boreholes water sellers in Lomé (in French PRRESAF) was implemented to contribute to the guarantee of public health. One of its objectives is to improve the hydrological understanding of the shallow Continental Terminal (CT) aquifer tapped by water sellers. It is a vital water resource in the coastal sedimentary extending from Ghana to Nigeria. The results presented here are part of this project and aim at assessing the hydrological factors controlling CT groundwater quality and chemistry using principal component analysis (PCA), hierarchical cluster analysis (HCA), and GIS. High-resolution sampling campaigns for major ions water quality analyses were performed to improve the accuracy of factors assessment. The results showed that groundwater is predominantly acidic with varying degrees of mineralization ranging from very soft to brackish waters. The integration of multivariate results to GIS allows classifying samples into five main groups. They revealed the probable recharge and discharge areas, associated hydrochemical evolution along flow paths, and areas under the high impact of land-use dynamics, wastewaters/sewage infiltration, and interactions with surface water systems. This study appears useful for managing boreholes' water sellers' activity relative to the integrity of groundwater resources and public health.